A Systematic Review and Meta-Analysis of Moderate-to-Vigorous Physical Activity Levels in Children and Adolescents With and Without ASD in Inclusive Schools - Li, Ru; Liang, Xiao; Zhou, Yujuan; Ren, Zhanbing (Frontiers in Pediatrics, 2021)
Background: The health benefits of physical activity (PA) participation are well documented. Little was known about the PA levels of students with autism spectrum disorder (ASD) and their typically developing (TD) peers in inclusive schools. This study aimed to synthesize available studies examining PA levels of children and adolescents with and without ASD and its associated factors that affected their PA participation during inclusive schools applying the social-relational model of disability (SRMD). Methods: Eight databases were searched including CINAHL Complete, SPORTDiscus with Full Text, Pubmed, Embase, Web of Science, Eric, APA PsycINFO, and Scopus from inception through May 2021 to identify related studies. Two researchers independently screened studies, assessed methodological quality, and summarized relevant data. The McMaster Critical Reviewer Form for quantitative studies was used to evaluate the methodological quality of the included articles. Results: A total of seven articles were included in this systematic review. Overall, meta-analysis results indicated that children and adolescents with ASD had a moderately decreased PA levels compared to their TD peers (SMD=-0.585, 95% CI [-0.774, -0.425], p<.01). Individual, social, and environmental level factors that influence PA levels in children and adolescents with ASD were identified from the perspective of SRMD. Conclusion: This review indicates that children and adolescents with ASD have lower PA levels than their TD peers in inclusive schools and that multi-level factors affect their PA. Key words: physical activity, autism spectrum disorders, inclusive school, social-relational model of disability model, children